2018
DOI: 10.1016/j.psychsport.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Fight without sight: The contribution of vision to judo performance

Abstract: Objective: Although vision is typically considered the predominant sense for guiding performance, there are sports for which other senses are believed to be as important, if not more important than vision. Accordingly, in Paralympic judo, athletes with different degrees of vision impairment (VI) compete together based on the assumption that vision does not influence judo performance, as long as judokas start the match with their grip in place. The aim of this research was to test this assumption. Method: We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
43
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 28 publications
(34 reference statements)
8
43
0
1
Order By: Relevance
“…In addition, athletes with VI have been shown to have impaired postural balance, 28 with especially blind judokas suffering from performance disadvantages when competing with sighted or partially sighted athletes. 29 All of these attributes may increase the injury risk in this population, and it is recommended that training recommendations, medical support and future injury prevention strategies are specifically adapted to Paralympic judokas in order to create a safer sport.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In addition, athletes with VI have been shown to have impaired postural balance, 28 with especially blind judokas suffering from performance disadvantages when competing with sighted or partially sighted athletes. 29 All of these attributes may increase the injury risk in this population, and it is recommended that training recommendations, medical support and future injury prevention strategies are specifically adapted to Paralympic judokas in order to create a safer sport.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, it is doubtful whether the rule adaptations are sufficient to allow judokas with different degrees of VI to compete equitably against each other. Recent analyses of competition outcomes suggest that under the present system, blind judokas might be at a disadvantage when competing against partially sighted opponents (Krabben et al, 2018; Mashkovskiy et al, 2018). Yet no studies have been carried out which directly relate measures of functional vision to judo performance.…”
Section: Introductionmentioning
confidence: 95%
“…Blind athletes are afforded no handicapping or advantage during competition, with the classes only used for the purposes of allocating award ranking points for the World Ranking List on the basis of the match outcomes 3 . The rationale behind this historical choice to have a single competition in which athletes from all classes compete is that the adaptations to the competition rules in VI judo increase the likelihood that those with more impairment are not disadvantaged when competing against others with less impairment (Krabben et al, 2018). In the able-sighted equivalent, athletes commence their bout 4 m apart and must first compete to obtain an advantageous grip on their opponent before battling while in-contact.…”
Section: Introductionmentioning
confidence: 99%
“…Since judo athletes remain in contact with each other throughout a large part of the bout, periodically their vision can be obstructed when grappling. Krabben et al (2018) indicated that this sport might even be performed quite adequately without vision. Vision is typically considered the predominant sense for guiding performance as blind judo athletes perform worse in competition than their partially sighted opponents and sighted judo athletes perform worse when fighting blindfolded (Krabben et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Krabben et al (2018) indicated that this sport might even be performed quite adequately without vision. Vision is typically considered the predominant sense for guiding performance as blind judo athletes perform worse in competition than their partially sighted opponents and sighted judo athletes perform worse when fighting blindfolded (Krabben et al, 2018). Thus, including the absence of visual information on postural demands especially with fatigue could have an impact on performance.…”
Section: Introductionmentioning
confidence: 99%